P04.26 Robustness of capturing behavioural and sexual lifestyle data for a complex clinical study using internet-based computer assisted self-interview. (13th September 2015) - Nori, AV; Hay, PE; Butcher, PD; Sadiq, ST
Abstract : Introduction: Sexual behaviour and vaginal practices impact on vaginal pathology, but accurately capturing such data for multi-site clinical studies is logistically difficult. Computer assisted self-interviews (CASI), are useful for capturing sensitive information for community surveys but require programming expertise or expensive software. We piloted an open-source software designed internet-based CASI, using previously validated questions for a multi-site clinical study on the vaginal microbiome. Methods: The CASI question-structure was constructed from the third UK National Survey of Sexual Attitudes and Lifestyles using LimeSurvey open source software and consisted of 71 questions, delivered through a responsive algorithm, covering demographics, sexual behaviour, vaginal practices, contraception and life-time smoking history. Patients could decline questions and the CASI was delivered to participants online. Bacterial vaginosis (BV) status was determined by Nugent scores from Gram-stained lateral vaginal swab smears. Results: Data from 155 women with available Nugent scores were included. Mean time to completing CASI was 303 s (Range: 111.76 -670.15 s 95% CI ±16.83 s). There were no missing data. The question most participants declined to answer was "number of one-off partners" (14 participants, 9%). White ethnicity and oestrogen-based contraceptives were inversely related with BV (Odds ratios (OR): 0.33 [95% CI: 0.16–0.67] and 0.41 [0.17–0.97] respectively) and lifetime smoking of >1 pack-years and regular vaginal douching were directly related with BV (OR: 2.56 [1.21–5.41] and 2.03 [1.01–4.09] respectively). Nearly 50% of women reported daily vaginal douching and >90% reported using feminine care products in the preceding month. Conclusion: The CASI delivered a complete dataset, the findings from which were consistent with published associations of BV, demonstrating robustness. Web-based CASI is an efficient method of collecting sensitive sexual and behavioural data within a complex clinical study, from patients recruited in busy clinical settings, and can be developed using open-source questionnaire software without the need for coding expertise. Disclosure of interest statement: This work was done as part of the Electronic Self-Testing Instruments for Sexually Transmitted Infection (eSTI2) Consortium funded under the UKCRC Translational Infection Research (TIR) Initiative supported by the Medical Research Council (Grant Number G0901608). The funding sources had no involvement in the study design or conduct; the collection, analysis and interpretation of data; the preparation, review or approval of the manuscript; or the decision to submit the manuscript for publication. The views expressed are those of the authors and not necessarily those of the NHS, the MRC, or St George's, University of London. The authors declare no competing interests.